2010
DOI: 10.5195/jwsr.2010.460
|View full text |Cite
|
Sign up to set email alerts
|

Horizontalist Youth Camps and the Bolivarian Revolution: A Story of Blocked Diffusion

Abstract: Between 2001 and2005, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Much has been made of the ability of Spanish 15-M activists to manage deliberative consensus-based assemblies of up to 5000 participants. Research on movement learning processes (Doerr, 2009;Polletta, 2002;Romanos, 2013) demonstrates that these abilities cannot be convincingly explained by commitment to principles or by transnational diffusion processes leading to the wholesale 'adoption' of practices (Wood, 2010). In fact, the effective management of large deliberative assemblies has been a key challenge of social movements in Spain over the past two decades, and the adoption of deliberative techniques has been slow and arduous, not least because of resistance from institutional left actors and the strong influence of institutional left actors on social movement cultural practices (Flesher Fominaya, 2005, 2007a.…”
Section: Movement Continuity: a Genealogical Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…Much has been made of the ability of Spanish 15-M activists to manage deliberative consensus-based assemblies of up to 5000 participants. Research on movement learning processes (Doerr, 2009;Polletta, 2002;Romanos, 2013) demonstrates that these abilities cannot be convincingly explained by commitment to principles or by transnational diffusion processes leading to the wholesale 'adoption' of practices (Wood, 2010). In fact, the effective management of large deliberative assemblies has been a key challenge of social movements in Spain over the past two decades, and the adoption of deliberative techniques has been slow and arduous, not least because of resistance from institutional left actors and the strong influence of institutional left actors on social movement cultural practices (Flesher Fominaya, 2005, 2007a.…”
Section: Movement Continuity: a Genealogical Approachmentioning
confidence: 97%
“…The processes of transnational movement culture diffusion are much less immediate or Debunking spontaneity 9 spontaneous than many accounts would suggest. Research shows that new practices must be adapted to local and national cultural repertoires through processes of cultural translation (Doerr, 2009) and are by no means always successful (Wood, 2010).…”
Section: Tracing Movement Culture Continuitymentioning
confidence: 99%
“…Transnational cultural diffusion processes are not spontaneous or immediate, however logical or brilliant the innovation (Chabot and Duyvendak ). Wood () and Malets and Zajak () have shown that cultural translation processes are crucial to the diffusion of social movement practices, ideas, and frames. These often fail because of perceived or actual incompatibility between local and “new” extra‐local or transnational movement cultures.…”
Section: Transnational Encounters: Meetings and Assembliesmentioning
confidence: 99%
“…In this language of spaces of flows (Castells ) and cross‐contamination, factors that facilitate transnational networking and that transnational activists share are stressed, but with important exceptions (eg Chabot and Duyvendak ; Cumbers et al ; Doerr , ; Routledge ; Wood , ), less attention has been paid to barriers to transnationalism and to differences , particularly cultural differences between activists as important in hindering the dynamics of transnational networking (Doerr ). Such cultural factors are rarely studied empirically (Doerr ) and the role of the nation, and “place” in shaping movement subcultures is also understated (Baumgarten ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation